Implementation of Results-Based Performance Management System: An Approach for Social Change in the Educational System - Catalogo, Mabe; Doromal, Araceli (Technium Social Sciences Journal, 2022)
Performance Management System (PMS) is instrumental to employees’ productivity and organizational competence. Entering into the quality assurance era, the Department of Education (DepEd) engaged in a paradigm shift in its management system and executed Results-Based Performance Management System (RPMS). Thus, this descriptive study assessed the extent of RPMS implementation in selected schools in the Philippines. Using the questionnaire adopted from DepEd Order No. 2, series of 2015, data were collected from 862 assessors involving teachers, headteachers, and supervisors. Employing descriptive analysis, findings showed the great extent of RPMS implementation in general, and according to classification, school level, and position of assessors. It also revealed that the four RPMS phases are implemented to a great extent, though a subsidence of execution of the work processes is noted as the phases progress. Also, certain practices were superficially carried out and implementation challenges were apparent. This signifies opportunities for improvement in the management system. Thus, the department should create cluster performance management teams, reassess the implementing guidelines, and organize technical assistance trainings to set foot towards total quality implementation and further actuate social change.